Efficacy and Safety of Oritavancin Relative to Vancomycin for Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI) in the Outpatient Setting: Results From the SOLO Clinical Trials. (19th January 2017) - Lodise, Thomas P.; Redell, Mark; Armstrong, Shannon O.; Sulham, Katherine A.; Corey, G. Ralph
Abstract: Background: The objective of this analysis was to evaluate the efficacy and safety of oritavancin compared with vancomycin for patients with acute bacterial skin and skin structure infections (ABSSSIs) who received treatment in the outpatient setting in the Phase 3 SOLO clinical trials. Methods: SOLO I and SOLO II were 2 identically designed comparative, multicenter, double-blind, randomized studies to evaluate the efficacy and safety of a single 1200-mg dose of intravenous (IV) oritavancin versus 7–10 days of twice-daily IV vancomycin for the treatment of ABSSSI. Protocols were amended to allow enrolled patients to complete their entire course of antimicrobial therapy in an outpatient setting. The primary efficacy outcome was a composite endpoint (cessation of spread or reduction in size of the baseline lesion, absence of fever, and no rescue antibiotic at early clinical evaluation [ECE]) (48 to 72 hours). Key secondary endpoints included investigator-assessed clinical cure 7 to 14 days after end of treatment (posttherapy evaluation [PTE]) and 20% or greater reduction in lesion area at ECE. Safety was assessed until day 60. Results: Seven hundred ninety-two patients (oritavancin, 392; vancomycin, 400) received entire course of treatment in the outpatient setting. Efficacy response rates at ECE and PTE were similar (primary composite endpoint at ECE: 80.4% vs 77.5% for oritavancin and vancomycin, respectively) as was incidence of adverse events. Five patients (1.3%) who received oritavancin and 9 (2.3%) vancomycin patients were subsequently admitted to a hospital. Conclusions: Oritavancin provides a single-dose alternative to multidose vancomycin for treatment of ABSSSI in the outpatient setting.